Barriers and Best Practices of Twitter for Professional Learning: A Qualitative Study of Missouri Principal Perceptions - Powers, Bill (Southwest Baptist University, 2016)
Educators seek professional learning to meet their personal needs and the needs for their students each year. However, many times the professional learning is not tailored to the audience and the costs to attend conferences does not lend itself to being effective use of time and resources. Many educators are now turning to Twitter for professional learning. Twitter allows the user to login anytime and anyplace to connect and learn with others on topics of their choosing. Social media is a growing medium educators are using to eliminate the need to travel and reduce costs associated with conferences. Much of the research to this point has focused on how teachers use Twitter for learning. Through this research, the researcher sought the answers to two research questions around the learning of principals: 1.) What are the barriers keeping Missouri’s current public school principals serving in prekindergarten through twelfth grade buildings from using Twitter for professional learning? and 2.) What are best practices for managing barriers to using Twitter as a professional learning tool? The design of this qualitative study allowed the researcher to gather data from 539 leaders in Missouri and from in-depth interviews with six individuals to address the research questions. Through the work the researcher found the barriers principals encountered were lack of time, feeling confused or overwhelmed, and the limited characters within Twitter. Respondents noted best practices to using Twitter were resource acquiring and sharing resources, ability for collaboration, networking, and participating in chats, and using Twitter as a public relations tool for their school.